An audit on patients undergoing bone densitometry in a Sri Lankan Family Practice - Fernando, G.V.M.C.; Jayawardana, R.R.; De Silva, H.L.; Samaranayaka, T.S.P.; Alahakoon, C.; Jeewandara, C.J. (WoncaSAR 2016, 2016)
Attached

Introduction and Objectives: Osteoporosis is major risk factor for morbidity and mortality in the elderly and its prevalence increases with age. In Sri Lanka due to limited availability of bone densitometries scanning and high cost many elderly do not have access to bone mineral density (BMD) testing. Therefore high risk patients cannot be identified. Since April 2015 the Family Practice Centre, University of Sri Jayewardenepura, BMD testing has been available at a low cost. The aim of this audit was to identify patients with osteoporosis or osteopenia undergoing screening at Family Practice Centre. Method: Patient medical records from the inception of BMD testing services were retrospectively audited using simple statistics. Management was seen for concordance with NICE guidelines. Results: The audit included 117 patients both males and females (n=102) with a mean age of 59.95 years, 17.1% (n=20) of patients had osteoporosis and 38.5% had osteopenia of the hip and 35.9% (n=42) had osteoporosis and 37.6% had osteopenia at the spine. Two patients were on medication for osteoporosis. The mean 10 year overall fracture risk was 1.435% and that for hip was 0.274%. Depending on these two indices the number needed to treat was 1. Recommendations :Family physicians (FP) have a pivotal role in the prevention and early identification of osteoporosis. So far adherence to guidelines has been minimal. This could be due to limited availability of BMD testing and lack of active screening for osteoporosis. Awareness and availing the service at a low cost would lead to improved patient outcomes.